Empat Tokoh Penyair Arab Masa Jahiliyah: Bag.2 - Azhari, Arina Fitriya (Maliki Interdisciplinary Journal, 2025)
The Arab poets of the Jahiliyyah, i.e. pre-Islamic period, who played an important role in the development of Arabic literature. At that time, poetry not only served as entertainment, but also as a means to convey social values, tribal pride, and social criticism. Social values, tribal pride, and social criticism. Some of the major poetic figures discussed include Labid Ibn Rabiah, Amr Ibn Kalthum, Tharfah Ibn ’Abd, and Al-Haris Ibn Hilza. Labid Ibn Rabiah is known for his works that depict everyday life and heroic values, and his transition from themes of tribal pride to Islamic spirituality. Amr Ibn Kalthum, a leader of the Taghlib tribe, wrote a poem of pride that highlighted the courage and honor of his tribe. Tharfah Ibn ’Abd described the nomadic life in the desert through descriptive poetry, often with a tones of melancholy and social criticism. Al-Haris Ibn Hilza used poetry as a diplomatic means to defend the honor of his tribe before the king. Overall, their works enriched Arabic literature with themes of heroism, nature, tribal pride, as well as spiritual and social reflections, which highlighting the values of life during the Jahiliyyah period.